Non-technical risks and their impact on the mining industry - Trench, Allan; Packey, Daniel J.; Sykes, John (The Australasian Institute of Mining and Metaullurgy, 2014)
'Country risk', including the threat of 'resource nationalism', market-related 'commodity price risk' and corporate-level 'going concern risk' are identified as amongst the principal non-technical risk types having the greatest impact on the mining industry. 'Exchange rate risk' acts alongside commodity price risk at the corporate level where mine-related revenues are in United States dollars (US$) and the mine cost-base in a local currency. Other market-related risks comprise the various indirect price-influencing forces that drive mineral demand and the non-technical (market) factors that impact on the cost and volume of mineral supply. On the demand side these forces include the strength of the global economy, threat of substitution for key end-uses, changes in metal use patterns in the community and the role of government intervention on mineral demand. On the supply side issues of input costs, market structure and potential government-imposed restrictions are amongst the industry-level non-technical risks. Non-technical risks cannot be entirely isolated from technical risks in any overarching risk classification system applied to the mining industry. The technical and non-technical risk 'domains' inevitably overlap when the root causes of adverse outcomes are examined at both mine-project and company-levels. This paper reviews the various sources of non-technical risk, the interplay of non-technical and technical risks and observations on risk-related challenges facing the mining sector. Challenges in the non-technical risk domain include the effective communication of non-technical risks and their impacts to industry stakeholders as well as the mitigation of non-technical risks.